A systematic approach to rehabilitation for hemimaxillectomy patient - Rizwana Mallick; Shabina Sachdeva; Eram Perwez; Vishal Goyal; Vanshika Jain (Wolters Kluwer Medknow Publications, 2020)
Any surgical intervention for the correction of maxillofacial disorders consequently leads to a compromised functionality, esthetics, and patient's general quality of life. Larger defects requiring partial or complete excision of the affected part need prosthetic rehabilitation to restore patient's standard of living. Among the team of involved doctors, a prosthodontist plays a major role in the presurgical treatment planning and postsurgical rehabilitation of such patients. This following case report illustrates the various clinical and laboratory procedures that goes in pre- and post-surgical planning and rehabilitation of patient undergone hemi-maxillectomy, with an obturator prosthesis.